Batch Sedimentation Studies for Freshwater Green Alga Scenedesmus abundans Using Combination of Flocculants - Moorthy, Raghu K.; Premalatha, M.; Arumugam, Muthu (Frontiers in Chemistry, 2017)
Microalga is the only feedstock that has the theoretical potential to completely replace the energy requirements derived from fossil fuels. However, commercialization of this potential source for fuel applications is hampered due to many technical challenges with harvesting of biomass being the most energy intensive process among them. The fresh water microalgal species, Scenedesmus abundans, has been widely recognized as a potential feedstock for production of biodiesel (Mandotra et al., 2014). The present work deals with sedimentation of algal biomass using extracted chitosan and natural bentonite clay powder as flocculant. The effect of flocculant combination and different factors such as temperature, pH and concentration of algal biomass on sedimentation rates has been analyzed. A high flocculation efficiency of 76.22 + 7.81% was obtained at an algal biomass concentration of 1 + 0.05 g/L for a settling time of 1 hour at 50 + 5oC with a settling velocity of 103.2 + 0.6 cm/h and a maximum surface conductivity of 2260 + 2 µS/cm using an optimal design in response surface methodology (RSM). Biopolymer flocculant such as chitosan exhibited better adsorption property along with bentonite clay powder that reduced the settling time significantly.